INTEGRASI ISLAM DAN SAINS: MENGURAI DIKOTOMI ILMU MENUJU PARADIGMA TAUHID - Firdaus; Intan Rosari Andini; Hasbi Ash Shodiqin; Hanifah Hafshoh; Nazwa felinda Berutu; Satrio Syahbana; Adisty Puji Nurjayanti; Radhiyatul Fithri (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
The dichotomy between religious sciences and general sciences remains a significant issue in Islamic education. This separation causes knowledge to develop partially and limits the integration of intellectual and spiritual values. In the Islamic perspective, all knowledge originates from Allah SWT and should contribute to the welfare of humanity. This study aims to examine the historical roots of the dichotomy of knowledge, various models of Islam and science integration, their implementation in education, and the challenges faced in realizing an integrated scientific paradigm. This research employs a qualitative library research method by analyzing relevant books, journals, and academic literature. The findings indicate that the dichotomy of knowledge emerged due to historical factors such as colonialism, the dualistic education system, and the stagnation of intellectual development within the Muslim community. As a solution, several integration models have been proposed, including the Islamization of knowledge, Islamic science, the integrative-interconnective approach, scientific exegesis (tafsir ilmi), and revelation-based science. The implementation of these models in education can foster a more holistic understanding of the relationship between scientific knowledge and Islamic values. Although various challenges remain, the integration of Islam and science has the potential to become an educational paradigm capable of producing knowledgeable, ethical, and competitive generations in the modern era.